De re aedificatoria orders systematization shape grammar. - filipe coutinho quaresma; José P. Duarte; Mário Kruger (Joelho)
The paper will show parts of a shape grammar that uses as corpus the Alberti`s treatise and buildings to see possible influence in Portuguese Architecture. The column systematisation grammar is a grammar of detail and some of the different elements of the column system (base, shaft, capital and entablature) may be connected with different orders (Doric, Ionic, Corinthian and Composite) showing different combinations. This system may be applied to generate some buildings namely Rucellai Loggia and palace facade, Santa Maria Novella Facade, Santa Andrea and specifically the subject of this paper the central nave longitudinal façade of the church São Vicente de Fora in Lisboa. Finally transformations rules are analysed mapping Alberti`s treatise influence in the work of the authors of the generated building.